The Effectiveness of Cooperative Learning Strategy to Increase the Speaking Skill at the Nineth Grade Students of SMPN 1 Kokoda - Lokollo, Elvien (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
This research aims to determine the effectiveness of cooperative learning in enhancing the speaking ability of students at SMPN 1 Kokoda. This study utilized pre-experimental research using a sample of 25 students from 9A class. The data were gathered through a speaking test. The pupils' English speaking learning accomplishment data was acquired using monologue. The data were examined using descriptive methods. The data analysis showed that cooperative learning considerably improved students' speaking achievement following the treatment. Cooperative learning significantly improved students' English-speaking achievement compared to conventional activities, as demonstrated by the t-test value of 24.403 and the p-value of 0.000, which was below the 0.5 level of significance. In conclusion, the implementation of Cooperative Learning strategy improved the students’ speaking skills.